Zahtevnost izpitne pole 1 pri slovenščini na poklicni maturi 2002-2013 - Godec Soršak, Lara (Jezik in slovstvo, 2015)
The paper presents findings based on reports on the Vocational Matura from 2002 to 2013, focusing on Test Paper 1 of the written exam in the Slovenian language. The goal is to identify which exercises in Test Paper 1 cause the most problems for candidates, in order to determine which activities deserve more attention in Slovenian language classes in high school.
Keywords: Slovene; slovenščina; poklicna matura; srednje šole; maturitetni izpiti; analize